The absence of seroconversion after exposition to hepatitis C virus is not related to KIR-HLA genotype combinations (GEHEP-012 study). - Martín-Sierra, Carmen; Bravo-Romero, María José; Saez, Maria Eugenia; De Rojas, Itziar; Santos, Marta; Martín-Carmona, Jesica; Corma-Gómez, Anaïs; González-Serna, Alejandro; Royo-Sánchez-Palencia, José Luis; Pineda, Juan A.; Rivero, Antonio; Rivero-Juárez, Antonio; et al. (Elsevier, 2024)
Background & aims It has been reported that specific killer-cell immunoglobulin-like receptors (KIRs) and HLA genotype combinations, such as KIR2DS4/HLA-C1 with presence of KIRDL2 or KIRDL3, homozygous KIRDL3/HLA-C1 and KIR3DL1/≥2HLA-Bw4, are strongly associated with the lack of active infection and seroconversion after exposition to hepatitis C virus (HCV). Objective To determine whether these KIR-HLA combinations are relevant factors involved in that phenotype. Patients and methods In this retrospective case-control study, genotype data from a genome-wide association study previously performed on low susceptibility to HCV-infection carried out on 27 high-risk HCV-seronegative (HRSN) individuals and 743 chronically infected (CI) subjects were used. HLA alleles were imputed using R package HIBAG v1.2223 and KIR genotypes were imputed using the online resource KIR*IMP v1.2.0. Results It was possible to successfully impute at least one KIR-HLA genotype combination previously associated with the lack of infection and seroconversion after exposition to HCV in a total of 23 (85.2%) HRSN individuals and in 650 (87.5%) CI subjects. No KIR-HLA genotype combination analyzed was related to the HRSN condition. Conclusions Our results suggest that those KIR-HLA genotype combinations are not relevant factors involved in the lack of infection and seroconversion after exposition to HCV. More studies will be needed to completely understand this phenotype.
Keywords: Virus de la hepatitis C; Exposed uninfected; GWAS; Genetics; HLA; Hepatitis C virus; High-risk HCV-Seronegative; KIR